Association of methotrexate and tumour necrosis factor antagonists with risk of infectious outcomes including opportunistic infections in the CORRONA registry. Issue 2 (8th April 2009) - Greenberg, J D; Reed, G; Kremer, J M; Tindall, E; Kavanaugh, A; Zheng, C; Bishai, W; Hochberg, M C
Abstract : Objective: To examine the association of methotrexate (MTX) and tumour necrosis factor (TNF) antagonists with the risk of infectious outcomes including opportunistic infections in patients with rheumatoid arthritis (RA). Methods: Patients with RA enrolled in the Consortium of Rheumatology Researchers of North America (CORRONA) registry prescribed MTX, TNF antagonists or other disease-modifying antirheumatic drugs (DMARDs) were included. The primary outcomes were incident overall and opportunistic infections. Incident rate ratios were calculated using generalised estimating equation Poisson regression models adjusted for demographics, comorbidities and RA disease activity measures. Results: A total of 7971 patients with RA were followed. The adjusted rate of infections per 100 person-years was increased among users of MTX (30.9, 95% CI 29.2 to 32.7), TNF antagonists (40.1, 95% CI 37.0 to 43.4) and a combination of MTX and TNF antagonists (37.1, 95% CI 34.9 to 39.3) compared with users of other non-biological DMARDs (24.5, 95% CI 21.8 to 27.5). The adjusted incidence rate ratio (IRR) was increased in patients treated with MTX (IRR 1.30, 95% CI 1.12 to 1.50) and TNF antagonists (IRR 1.52, 95% CI 1.30 to 1.78) compared with those treated with other DMARDs. TNF antagonist use was associated with an increased risk of opportunistic infections (IRR 1.67, 95% CI 0.95 to 2.94). Prednisone use was associated with an increased risk of opportunistic infections (IRR 1.63, 95% CI 1.20 to 2.21) and an increased risk of overall infection at doses >10 mg daily (IRR 1.30, 95% CI 1.11 to 1.53). Conclusions: MTX, TNF antagonists and prednisone at doses >10 mg daily were associated with increased risks of overall infections. Low-dose prednisone and TNF antagonists (but not MTX) increased the risk of opportunistic infections.